Treatment of meniscal tears: An evidence based approach - Mordecai, Simon C (Baishideng Publishing Group Inc, 2014)
Treatment options for meniscal tears fall into three broad categories; non-operative, meniscectomy or meniscal repair. Selecting the most appropriate treatment for a given patient involves both patient factors (e.g., age, co-morbidities and compliance) and tear characteristics (e.g., location of tear/age/reducibility of tear). There is evidence suggesting that degenerative tears in older patients without mechanical symptoms can be effectively treated non-operatively with a structured physical therapy programme as a first line. Even if these patients later require meniscectomy they will still achieve similar functional outcomes than if they had initially been treated surgically. Partial meniscectomy is suitable for symptomatic tears not amenable to repair, and can still preserve meniscal function especially when the peripheral meniscal rim is intact. Meniscal repair shows 80% success at 2 years and is more suitable in younger patients with reducible tears that are peripheral (e.g., nearer the capsular attachment) and horizontal or longitudinal in nature. However, careful patient selection and repair technique is required with good compliance to post-operative rehabilitation, which often consists of bracing and non-weight bearing for 4-6 wk.